2007
DOI: 10.1016/j.bbmt.2006.09.010
|View full text |Cite
|
Sign up to set email alerts
|

High-dose Therapy with Single Autologous Transplantation versus Chemotherapy for Newly Diagnosed Multiple Myeloma: A Systematic Review and Meta-analysis of Randomized Controlled Trials

Abstract: Myeloablative high-dose therapy and single autologous stem cell transplantation (HDT) is frequently performed early in the course of multiple myeloma, supported by some randomized controlled trials (RCTs) indicating overall survival (OS) and progression-free survival (PFS) benefit compared with nonmyeloablative standard-dose therapy (SDT). Other RCTs, however, suggest variable benefit. We therefore undertook a systematic review and meta-analysis of all RCTs evaluating upfront HDT versus SDT in myeloma. The pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
131
2
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(141 citation statements)
references
References 34 publications
4
131
2
4
Order By: Relevance
“…This paradigm is supported by the results of multiple randomized trials demonstrating a higher complete remission rate and longer event-free survival in high-dose therapy recipients. 41 With the advent of novel induction therapies containing either bortezomib, lenalidomide or combinations that result in complete remission rates of up to 30% and VGPR rates of over 50%, the role of both single and tandem high-dose therapy consolidation for transplant eligible patients needs to be reexplored in the context of well designed clinical trials. An important aspect of new trials will be the role of planned up front transplant versus transplant at the time of subsequent relapse.…”
Section: Issues In Stem Cell Collectionmentioning
confidence: 99%
“…This paradigm is supported by the results of multiple randomized trials demonstrating a higher complete remission rate and longer event-free survival in high-dose therapy recipients. 41 With the advent of novel induction therapies containing either bortezomib, lenalidomide or combinations that result in complete remission rates of up to 30% and VGPR rates of over 50%, the role of both single and tandem high-dose therapy consolidation for transplant eligible patients needs to be reexplored in the context of well designed clinical trials. An important aspect of new trials will be the role of planned up front transplant versus transplant at the time of subsequent relapse.…”
Section: Issues In Stem Cell Collectionmentioning
confidence: 99%
“…Auto-HCT was associated with superior PFS and OS in two large randomized studies while a meta-analysis showed superior PFS. [1][2][3] Incorporation of auto-HCT and the introduction of the immunomodulatory drugs (ImiDs; thalidomide, lenalidomide and pomalidomide) and proteasome inhibitors (bortezomib and carfilzomib) have led to significant improvement in clinical outcomes, but cure has remained elusive. Allogeneic HCT (allo-HCT) studies demonstrated a plateau in OS with long-term follow-up, indicating a potential cure fraction.…”
Section: Introductionmentioning
confidence: 99%
“…1 MM remains incurable and the aim of treatment in non-elderly patients, in general o65 years, is to prolong survival using chemotherapy, corticosteroids and/or novel agents such as bortezomib or lenalidomide followed by high-dose chemotherapy and auto-SCT, which has been shown to be superior to conventional chemotherapy alone. [2][3][4] The optimal regimen to mobilize stem cells in patients with MM is still controversial and has not been clearly defined. The mobilization strategies implemented by most transplant centers consist of G-CSF alone (steady-state strategy) or CY followed by G-CSF (chemo-mobilizing strategy).…”
Section: Introductionmentioning
confidence: 99%